A quasi-real-time inertialess microwave holographic imaging system - Nilsen, Christopher S (Department of Electrical Engineering, 2016)
This thesis records the theoretical analysis and hardware development of a laboratory microwave imaging system which uses holographic principles. The application of an aperture synthesis technique and the electronic commutation of all antennae has resulted in a compact and economic assembly - which requires no moving parts and which, consequently, has a high field mapping speed potential. The relationship of this microwave holographic system to other established techniques is examined theoretically and the performance of the imaging system is demonstrated using conventional optically- and numerically-based reconstruction of the measured holograms. The high mapping speed potential of this system has allowed the exploitation of an imaging mode not usually associated with microwave holography. In particular, a certain antenna array specification leads to a versatile imaging system which corresponds closely in the laboratory scale to the widely used synthetic aperture radar principle. It is envisaged that the microwave holographic implementation of this latter principle be used as laboratory instrumentation in the elucidation of the interaction of hydrodynamic and electromagnetic waves. Some simple demonstrations of this application have been presented, and the concluding chapter also describes a suitable hardware specification. This thesis has also emphasised the hardware details of the imaging system since the development of the microwave and other electronic components represented a substantial part of this research and because the potential applications of the imaging principle have been found to be intimately linked to the tolerances of the various microwave components. Bibliography: pages 122-132.